THE SEMANTIC PROSODY ANALYSIS OF ‘INCREASE’ IN COVID-19: A CORPUS-BASED STUDY - Sulalah, Anis (Lire Journal (Journal of Linguistics and Literature), 2020)
Abstract: Increase is a neutral word that is generally perceived as a positive word, were synonymous with positive words such as rise, grow, expand. However, when resorting to dictionary definitions, increase has been found to possess negative words such as 'increase the violence'. This study investigates how 'increase', generally often categorized with positive words, interacts with neighboring words to achieve particular meanings and how particular forms of several words can change a word to negative, positive and neutral connotation. This study is analyzed on a descriptive qualitative research design because corpus linguistic research needs to be interpreted more with qualitative considerations. The data are collected using a corpus-based approach, Covid-19 corpora, and the data analysis using semantic prosody based on Stubbs's (1998) theory. The result of the data showed that word increase in Covid-19 corpora have negative meaning if it is collocated with several word such as risk, rate, levels, number, significantly and associated and followed by negative word but it will have positive meaning if it is located with word expression.